Composite solid electrolyte, preparation method thereof, solid-state battery and electric device
Patent Information
- Application Number
- CN202611251387.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
现有复合电解质在面对高活性锂金属负极和高电压正极时,难以同时满足两侧截然不同的界面要求(负极需高还原稳定性,正极需高氧化稳定性),界面副反应和锂枝晶生长问题依然突出
1.空间梯度匹配,双向界面稳定:本申请的复合固态电解质在厚度方向上具有组成和功能连续渐变的非对称结构,通过结构梯度设计,使电解质在面向正极一侧具有更高的抗氧化性和模量以稳定高电压界面,在面向负极一侧具有更高的还原稳定性和柔韧性以促进锂均匀沉积,从根源上降低了双向界面阻抗和副反应。
Smart Images

Figure SMS_8
Abstract
Description
Technical Field
[0001] This application belongs to the field of electrochemical energy storage device technology, specifically relating to a composite solid electrolyte and its preparation method, solid-state battery and electrical equipment. Background Technology
[0002] Solid-state batteries are considered a key technology for next-generation high-energy-density energy storage systems. Their core component, the solid-state electrolyte, needs to simultaneously possess high ionic conductivity, excellent electrode interface stability, and good mechanical strength. However, current technologies still face significant challenges: Inorganic solid electrolytes such as oxides and sulfides have high ionic conductivity and high mechanical strength, but they have a solid-solid contact with the electrodes, resulting in high interfacial impedance, poor contact, and are prone to cracking due to volume changes during cycling, leading to performance degradation.
[0003] PEO-based and other polymer solid electrolytes are characterized by good flexibility and improved interfacial contact, but they have low room temperature ionic conductivity, narrow electrochemical window, and weak ability to suppress lithium dendrites.
[0004] To address the challenges of inorganic and polymer solid-state electrolytes, existing technologies have proposed composite electrolytes. However, current composite electrolytes struggle to simultaneously meet the distinct interface requirements of both the highly active lithium metal anode and the high-voltage cathode (the anode requires high reduction stability, while the cathode requires high oxidation stability). Interface side reactions and lithium dendrite growth remain significant issues. Summary of the Invention
[0005] The purpose of this application is to provide a composite solid electrolyte and its preparation method, a solid battery, and an electrical device to solve the above-mentioned problems.
[0006] To achieve the above objectives, this application adopts the following technical solution: In a first aspect, this application provides a composite solid electrolyte, comprising: a framework material, a deep eutectic electrolyte, a polymer, and an interface additive; The skeleton material includes fast ion conductors and ceramic fillers, and the materials forming the polymer include curable monomers and initiators. The composite solid electrolyte includes a first surface and a second surface arranged opposite to each other, the first surface facing the negative electrode and the second surface facing the positive electrode; the pore size of the first surface is smaller than the pore size of the second surface.
[0007] In some embodiments, the fast ion conductor includes at least one of LLZO, LATP, and LAGP; In some embodiments, the D50 of the fast ion conductor is 5–10 μm; The ceramic filler includes at least one of AlF3, BN, MgO, and TiO2, and the particle size of the ceramic filler is 50-100 nm.
[0008] And / or, the mass ratio of the fast ion conductor to the ceramic filler is (5-9):(1-5); And / or, the mass of the fast ion conductor and ceramic filler accounts for 30% to 60% of the total mass of the fast ion conductor and ceramic filler, deep eutectic electrolyte, curable monomer, and initiator.
[0009] In some embodiments, the deep eutectic electrolyte includes a lithium salt, a hydrogen bond donor, and a hydrogen bond acceptor; The lithium salt includes at least one of LiTFSI, LiFSI, LiPF6, and LiClO4; The hydrogen bond donor includes at least one of urea, acetamide, glycerol, and ethylene glycol; The hydrogen bond acceptor includes at least one of succinic anion, choline chloride, choline bromide, and tetrabutylammonium chloride.
[0010] And / or, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor and the lithium salt is 1:(1.5-3):(0.1-0.6).
[0011] In some embodiments, the curable monomer includes at least one of acrylate monomers, epoxy monomers, and olefin monomers, for in-situ curing.
[0012] And / or, the mass of the curable monomer accounts for 1% to 5% of the total mass of the deep eutectic electrolyte and the curable monomer; And / or, the initiator accounts for 0.1% to 1% of the total mass of the deep eutectic electrolyte, the curable monomer, and the initiator.
[0013] In some embodiments, the interface additive includes at least one of tin halide, bismuth halide, and zinc halide. The interface additive can react with lithium metal at the negative electrode during the first charge and discharge of the battery, generating a stable solid electrolyte interface film and / or a lithium-affinity alloy phase in situ. And / or, the mass of the interface additive accounts for 0.1% to 5% of the total mass of the raw materials forming the composite solid electrolyte; And / or, the thickness of the composite solid electrolyte is 50 μm to 300 μm.
[0014] Secondly, this application provides a method for preparing the above-mentioned composite solid electrolyte, comprising the following steps: Lithium salt, hydrogen bond donor and hydrogen bond acceptor are mixed and heated and stirred until a clear, transparent and homogeneous liquid is obtained, which is a deep eutectic electrolyte; The deep eutectic electrolyte, curable monomer, initiator, interfacial additive, fast ion conductor and ceramic filler are mixed to obtain a slurry; The slurry is injected into a mold, and the slurry is frozen and solidified under a unidirectional temperature gradient to obtain a frozen preform; The frozen preform is freeze-dried to obtain a porous intermediate. The porous intermediate is solidified to obtain a composite solid electrolyte.
[0015] In some embodiments, when preparing a deep eutectic electrolyte, the heating temperature is 40°C to 90°C; And / or, the temperature difference of the unidirectional temperature gradient is 20℃~70℃.
[0016] And / or, the preparation of a frozen preform includes: injecting the slurry into a mold, placing the bottom of the mold on a cold source at -40°C to -10°C, exposing the upper part of the mold to a preset temperature environment, wherein the preset temperature is higher than the temperature of the cold source, forming a unidirectional temperature gradient, and allowing it to stand for 2 to 8 hours to obtain a frozen preform.
[0017] In some embodiments, the freeze-drying temperature is -60°C to -40°C, the freeze-drying is carried out under a vacuum of 5 Pa to 20 Pa, and the freeze-drying time is 24 to 72 hours; And / or, the solidification treatment of the porous intermediate includes: irradiating the porous intermediate with ultraviolet light to solidify the porous intermediate and obtain a composite solid electrolyte, wherein the wavelength of the ultraviolet light is 200-400 nm and the irradiation time of the ultraviolet light is 10-60 minutes.
[0018] Thirdly, this application provides a solid-state battery, including a positive electrode, a negative electrode, and a composite solid-state electrolyte disposed between the positive electrode and the negative electrode; wherein the composite solid-state electrolyte is the composite solid-state electrolyte described above or a composite solid-state electrolyte prepared by the preparation method described above.
[0019] Preferably, the negative electrode comprises a lithium metal negative electrode or a silicon-based negative electrode; the positive electrode comprises a high-nickel ternary material, a lithium-rich manganese material, a lithium manganese iron phosphate material, or a lithium iron phosphate material.
[0020] Fourthly, this application also provides an electrical device, which includes the solid-state battery described above.
[0021] Compared with the prior art, the beneficial effects of this application include: 1. Spatial gradient matching and bidirectional interface stability: The composite solid electrolyte of this application has an asymmetric structure with continuous and gradual changes in composition and function in the thickness direction. Through structural gradient design, the electrolyte has higher oxidation resistance and modulus on the positive electrode side to stabilize the high voltage interface, and higher reduction stability and flexibility on the negative electrode side to promote uniform lithium deposition, thereby reducing bidirectional interface impedance and side reactions from the root.
[0022] 2. Three-dimensional continuous ion pathway, synergistic conduction and mechanics: The interpenetrating network constructed from a gradient-distributed framework material provides a continuous and rapid lithium-ion conduction channel. From the negative electrode side to the positive electrode side, the gradual design of porosity and modulus achieves a uniform distribution of the ion flow field and a smooth transition of mechanical stress, effectively suppressing local current concentration and dendrite penetration.
[0023] 3. In-situ adaptive interface construction: By introducing interface additives, the interface can react with lithium on the negative electrode during the first cycle of the battery to generate a stable solid electrolyte interface film and a lithium-loving alloy layer in situ. This achieves adaptive construction and dynamic strengthening of the interface, and greatly improves cycle reversibility.
[0024] 4. Innovative Process and Controllable Structure: Utilizing directional cryogenic casting technology, a gradient structure is intrinsically constructed using a physical field (temperature gradient). This method is simple, controllable, and avoids the interlayer delamination problems associated with multi-layer coatings. Subsequent in-situ curing steps solidify the liquid components, ensuring the macroscopic solid-state properties and excellent mechanical integrity of the electrolyte.
[0025] 5. Excellent overall performance: The solid electrolyte membrane prepared in this application combines high ionic conductivity, wide electrochemical window, good flexibility and excellent thermal stability. The assembled solid-state battery has significant improvements in cycle performance, rate performance and safety. Detailed Implementation
[0026] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0027] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0028] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.
[0029] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.
[0030] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (where K is any number representing a multiplier). It is important to understand that, unlike parts by mass, the sum of the mass parts of all components is not limited to 100 parts.
[0031] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0032] Existing solid electrolyte membranes have drawbacks such as the inability to simultaneously achieve high ionic conductivity, high mechanical strength, and stable compatibility with highly active electrodes (such as lithium metal anodes and high-voltage cathodes).
[0033] To address the aforementioned technical problems, this application provides a composite solid electrolyte, which comprises a framework material, a deep eutectic electrolyte, a polymer, and interfacial additives. The backbone material includes fast ion conductors and ceramic fillers, and the materials forming the polymer include curable monomers and initiators; The composite solid electrolyte includes a first surface and a second surface arranged opposite to each other, the first surface facing the negative electrode and the second surface facing the positive electrode; the pore size of the first surface is smaller than the pore size of the second surface.
[0034] In some embodiments, the pore size of the composite solid electrolyte varies gradient along the thickness direction.
[0035] In some embodiments, the fast ion conductor includes at least one of LLZO, LATP, and LAGP; In some embodiments, the D50 of the fast ion conductor is 5–10 μm; The ceramic filler includes at least one of AlF3, BN, MgO, and TiO2.
[0036] In some embodiments, the particle size of the ceramic filler is 50–100 nm.
[0037] The mass ratio of the fast ion conductor to the ceramic filler is (5-9):(1-5); for example, the mass ratio of the fast ion conductor to the ceramic filler is any value between 5:1, 6:2, 7:3, 8:4, 9:5 or (5-9):(1-5).
[0038] The combined mass of the fast ion conductor and ceramic filler accounts for 30% to 60% of the total mass of the fast ion conductor and ceramic filler, deep eutectic electrolyte, curable monomer, and initiator. For example, the combined mass of the fast ion conductor and ceramic filler accounts for any value between 30%, 40%, 50%, 60%, or 30% to 60% of the total mass of the fast ion conductor and ceramic filler, deep eutectic electrolyte, curable monomer, and initiator.
[0039] In some embodiments, the deep eutectic electrolyte comprises a lithium salt, a hydrogen bond donor, and a hydrogen bond acceptor, wherein the lithium salt comprises at least one of LiTFSI, LiFSI, LiPF6, and LiClO4; the hydrogen bond donor comprises at least one of urea, acetamide, glycerol, and ethylene glycol; and the hydrogen bond acceptor comprises at least one of succinic anionyl nitrile, choline chloride, choline bromide, and tetrabutylammonium chloride.
[0040] The molar ratio of the hydrogen bond acceptor to the hydrogen bond donor and the lithium salt is 1:(1.5-3):(0.1-0.6). For example, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor and the lithium salt is any value between 1:1.5:0.1, 1:2:0.3, 1:2.5:0.5, 1:3:0.6 or 1:(1.5-3):(0.1-0.6).
[0041] In some embodiments, the curable monomer includes at least one of acrylate monomers, epoxy monomers, and olefin monomers, for in-situ curing.
[0042] In some embodiments, the acrylate monomers include dipentaerythritol pentaacrylate (DPPA).
[0043] And / or, the mass of the curable monomer accounts for 1% to 5% of the total mass of the deep eutectic electrolyte and the curable monomer; for example, the mass of the curable monomer accounts for any value between 1%, 2%, 3%, 4%, 5% or 1% to 5% of the total mass of the deep eutectic electrolyte and the curable monomer.
[0044] The initiator accounts for 0.1% to 1% of the total mass of the deep eutectic electrolyte, curable monomer, and initiator. For example, the initiator accounts for any value between 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or 0.1% to 1% of the total mass of the deep eutectic electrolyte, curable monomer, and initiator.
[0045] In some embodiments, the initiator includes Irgacure 819.
[0046] In some embodiments, the interface additive includes at least one of tin halide, bismuth halide, and zinc halide; tin halide includes tin iodide (SnI4), and bismuth halide includes bismuth iodide (BiI3).
[0047] Interface additives can react with lithium metal at the negative electrode during the first charge and discharge of the battery to generate a stable solid electrolyte interface film and / or a lithiophilic alloy phase in situ.
[0048] The mass of the interface additive accounts for 0.1% to 5% of the total mass of the raw materials forming the composite solid electrolyte; for example, the mass of the interface additive accounts for any value between 0.1%, 1%, 2%, 3%, 4%, 5% or 0.1% to 5% of the total mass of the raw materials forming the composite solid electrolyte.
[0049] The thickness of the composite solid electrolyte is 50 μm to 300 μm. For example, the thickness of the composite solid electrolyte is 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, or any value between 50 μm and 300 μm.
[0050] This application also provides a method for preparing the composite solid electrolyte as described above, comprising: Lithium salt, hydrogen bond donor and hydrogen bond acceptor are mixed and heated and stirred until a clear, transparent and homogeneous liquid is obtained, which is a deep eutectic electrolyte; The deep eutectic electrolyte, curable monomer, initiator, interfacial additive, fast ion conductor and ceramic filler are mixed to obtain a slurry; The slurry is injected into a mold, and the slurry is frozen and solidified under a unidirectional temperature gradient to obtain a frozen preform; The frozen preform is freeze-dried to obtain a porous intermediate. The porous intermediate is solidified to obtain a composite solid electrolyte.
[0051] Under the action of a unidirectional temperature gradient, the solvent in the slurry crystallizes and grows in a directional manner along the temperature gradient direction, forcing the components to accumulate and rearrange in the gaps between the growing ice crystals, thereby forming a frozen preform with a gradient structure corresponding to the temperature field. By freeze-drying, the ice crystal template in the frozen preform can be removed to obtain a porous intermediate with a gradient pore structure. Then, under the curing treatment conditions, the curable monomers in the porous intermediate can be initiated to undergo an in-situ polymerization reaction, thereby permanently curing the entire gradient structure and obtaining a self-supporting solid electrolyte.
[0052] In some embodiments, when preparing a deep eutectic electrolyte, the heating temperature is 40°C to 90°C; For example, the heating temperature during the preparation of the deep eutectic electrolyte is 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, or any value between 40°C and 90°C.
[0053] The temperature difference of the unidirectional temperature gradient is 20℃~70℃; for example, the temperature difference of the unidirectional temperature gradient is 20℃, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃ or any value between 20℃ and 70℃.
[0054] The preparation of the frozen preform includes: injecting the slurry into a mold, placing the bottom of the mold on a cold source at -40℃ to -10℃, exposing the upper part of the mold to a preset temperature environment, wherein the preset temperature is higher than the temperature of the cold source to form a unidirectional temperature gradient, and letting it stand for 2 to 8 hours (e.g., 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours or any value between 2 and 8 hours) to obtain the frozen preform.
[0055] For example, the temperature of the cold source is any value between -40℃, -35℃, -30℃, -25℃, -20℃, -15℃, -10℃, or -40℃ to -10℃.
[0056] In some embodiments, the preset temperature environment is room temperature, and the preset temperature is 25°C.
[0057] In some embodiments, the freeze-drying process is carried out at a temperature of -60°C to -40°C, under a vacuum of 5 Pa to 20 Pa (e.g., 5 Pa, 10 Pa, 15 Pa, 20 Pa, or any value between 5 Pa and 20 Pa), and for a duration of 24 to 72 hours.
[0058] For example, the freeze-drying temperature is any value between -60℃, -55℃, -50℃, -45℃, -40℃, or -60℃ to -40℃; the freeze-drying time is any value between 24 hours, 28 hours, 30 hours, 33 hours, 35 hours, 38 hours, 40 hours, 43 hours, 45 hours, 48 hours, 50 hours, 53 hours, 55 hours, 58 hours, 60 hours, 63 hours, 65 hours, 68 hours, 70 hours, 72 hours, or 24 to 72 hours.
[0059] The solidification process of the porous intermediate includes: irradiating the porous intermediate with ultraviolet light to solidify the porous intermediate and obtain a composite solid electrolyte, wherein the wavelength of the ultraviolet light is 200-400 nm and the irradiation time of the ultraviolet light is 10-60 minutes.
[0060] For example, the wavelength of ultraviolet light is 200 nm, 250 nm, 300 nm, 350 nm, 400 nm or any value between 200 and 400 nm; the irradiation time of ultraviolet light is 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes or any value between 10 and 60 minutes.
[0061] In some embodiments, the power of the ultraviolet lamp is 100mW / cm². 2 .
[0062] This application also provides a solid-state battery, which includes a positive electrode, a negative electrode, and a composite solid-state electrolyte disposed between the positive electrode and the negative electrode. The composite solid-state electrolyte is either the composite solid-state electrolyte described above or a composite solid-state electrolyte prepared by the preparation method described above.
[0063] In some embodiments, the negative electrode includes a lithium metal negative electrode or a silicon-based negative electrode; the positive electrode includes a high-nickel ternary material, a lithium-rich manganese-based material, lithium manganese iron phosphate, or lithium iron phosphate.
[0064] Among them, high-nickel ternary materials include LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811).
[0065] This application also provides an electrical device, which includes the solid-state battery described above.
[0066] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0067] I. Preparation of composite solid electrolytes Example 1 Example 1 provides a composite solid electrolyte, the preparation method of which includes: (1) Material preparation: Preparation of the precursor: Succinate (SN), acetamide (ACM), and LiTFSI were mixed in a molar ratio of 1:2:0.3 and heated and stirred at 60°C until clear to obtain a deep eutectic electrolyte. 2 wt% of dipentaerythritol pentaacrylate (DPPA) as a curable monomer and 0.5 wt% of Irgacure 819 as a photoinitiator were added to the deep eutectic electrolyte to obtain the precursor.
[0068] Framework materials: micron-sized LLZO (D50 approximately 5μm), nano-sized aluminum fluoride (AlF3, particle size 50 nm, purity ≥99.9%).
[0069] Interface additive: Tin iodide (SnI4), purity 99.9%.
[0070] (2) Slurry preparation: Mix LLZO and nano AlF3 at a mass ratio of 7:3 and add them to the above precursor. The solid content is 40 wt%. Stir at high speed for 2 hours to form a uniform slurry. Add 1 wt% SnI4 to the slurry and continue stirring for 30 minutes.
[0071] (3) Gradient freezing molding: The slurry is injected into a polytetrafluoroethylene mold (inner cavity size: 50mm×50mm×2mm). The bottom of the mold is placed on a copper cooling platform at -30℃, and the upper part of the mold is exposed to a room temperature environment at 25℃ to form a unidirectional temperature gradient. The temperature difference of the unidirectional temperature gradient is 55℃. After standing for 4 hours, the slurry is completely solidified and frozen to obtain a frozen blank.
[0072] (4) Take out the frozen preform and put it into a freeze dryer for freeze drying. Dry it at -50℃ and 10Pa vacuum for 48 hours to completely remove the ice crystal template and obtain a porous intermediate.
[0073] (5) Then the porous intermediate was transferred to a nitrogen glove box and heated with a 365nm ultraviolet lamp (power 100mW / cm). 2 Irradiation for 30 minutes initiates the polymerization and solidification of DPPA monomers, resulting in a composite solid electrolyte with a thickness of approximately 120 μm.
[0074] The pore size of the composite solid electrolyte gradually decreases from about 5 μm to about 1 μm from the top surface (the side in contact with room temperature, i.e., the second surface) to the bottom surface (the side in contact with the cold source, i.e., the first surface).
[0075] Example 2 It is basically the same as Example 1, except that: nano AlF3 is replaced with nano boron nitride (BN), and the interfacial additive tin iodide (SnI4) in Example 1 is replaced with bismuth iodide (BiI3).
[0076] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that steps (3) and (4) are omitted, and step (5) is performed directly after step (2).
[0077] Comparative Example 2 (1) Material preparation: Polyethylene oxide (PEO, molecular weight 600,000 g / mol) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0078] (2) Preparation of pure polymer PEO-LiTFSI electrolyte: In an argon glove box (H2O / O2 < 0.1 ppm), PEO powder and LiTFSI were weighed at a molar ratio of EO:Li = 18:1, and anhydrous acetonitrile was added as a solvent in an amount equal to 6 times the total mass of the solids.
[0079] Stir magnetically at 60°C for 5 hours to form a homogeneous, transparent, viscous solution.
[0080] The solution was poured into a polytetrafluoroethylene mold and left to stand at room temperature for 12 hours. Then it was transferred to a vacuum drying oven at 45°C and dried for 36 hours to completely remove the residual solvent, resulting in a pure PEO-LiTFSI solid electrolyte membrane with a thickness of approximately 120 μm.
[0081] The obtained PEO-LiTFSI solid electrolyte membrane was annealed in a vacuum drying oven at 60°C for 12 hours to stabilize its crystalline morphology, and then transferred to a glove box for later use.
[0082] The room temperature ionic conductivity of Examples 1-2 and Comparative Examples 1-2 was tested, and the test results are shown in Table 1.
[0083] Room temperature ionic conductivity testing: The electrochemical impedance spectroscopy (EIS) method was used for testing. Example 1... 2. Comparative Example 1 The resulting electrolyte membrane was cut into circular pieces with a diameter of 10 mm, and gold (Au) was sputtered on both sides as blocking electrodes, with an effective area of 0.785 cm². 2 The sample was placed in a stainless steel symmetrical battery holder, and a torque of 5 N·m was applied to ensure interfacial contact. Testing was conducted using an electrochemical workstation (Gamry Reference 3000) in a 25±1℃ constant temperature chamber, with a frequency range of 0.1 Hz to 1 MHz and an AC perturbation amplitude of 10 mV. The bulk resistance R was obtained through equivalent circuit fitting (R(RQ) model). bulk Ionic conductivity is calculated using the following formula: σ=L / (R) bulk ×A) Where σ is the ionic conductivity (S / cm), L is the electrolyte membrane thickness (cm, measured at 5 evenly spaced points on the membrane using a micrometer and the average value is taken), and A is the effective electrode area (cm²). 2 Each group of samples was tested in parallel three times, and the average value was taken.
[0084] Example 1 2. Comparative Example 1 2. The prepared electrolyte membrane was cut into discs with a diameter of 16 mm and placed between a lithium metal anode (thickness 300 μm, diameter 15.6 mm) and an NCM811 cathode (area loading 12 mg / cm²). 2 CR2032 coin cells were assembled between 14 mm in diameter. Example 1... The first surface (smaller pore size side) of the composite solid electrolyte 2 faces the lithium metal anode, and the second surface (larger pore size side) faces the cathode.
[0085] Initial coulomb efficiency test: After the battery was placed in a constant temperature chamber at 25±1℃ for 2 hours, the battery testing system (Neware CT) was used. (4008) A constant current charge-discharge test was performed at a charge-discharge rate of 0.2C (1C = 180 mA / g, based on the mass of the NCM811 active material), with a voltage range of 2.7 V to 4.3 V. The initial coulombic efficiency was calculated using the following formula: Initial coulombic efficiency (%) = Initial discharge capacity / Initial charge capacity × 100%; Three batteries were assembled in parallel for each sample group, and the average value was taken.
[0086] Cycle count and capacity retention test: Constant current charge-discharge cycle test was conducted at 0.2C, 2.7 V to 4.3 V, and 25±1℃. The cycle termination condition was: the discharge capacity was lower than 80% of the initial discharge capacity. The number of cycles at which the termination condition was reached was recorded. The capacity retention rate was calculated using the following formula: Capacity retention rate (%) = Discharge capacity in the Nth cycle / Initial discharge capacity × 100%; Where N is the sequence number of the last cycle. Three batteries were assembled in parallel for each sample group, and the average value was taken.
[0087] Interfacial impedance growth rate test: Evaluation was performed using a comparative EIS test before and after cycling. Before cycling: After battery assembly, the battery was left to stand at 25±1℃ for 2 hours, and the initial EIS spectrum (frequency 0.1 Hz~1 MHz, amplitude 10 mV) was measured using an electrochemical workstation. After cycling: The battery was charged to an open circuit of 3.8 V, left to stand for 2 hours, and the EIS spectrum was measured again. The interfacial impedance R before and after cycling was extracted using equivalent circuit fitting. interface (The semicircular diameter in the mid-to-low frequency region corresponds to the sum of the interfacial charge transfer impedance and the SEI film impedance). The interfacial impedance growth rate is calculated using the following formula: Interface impedance growth rate (%) = (R) interface,after R interface,before ) / R interface,before ×100%; Three batteries were assembled in parallel for each sample group, and the average value was taken.
[0088] The test results are shown in Table 1 below.
[0089] Table 1. Comparison of room temperature electrochemical performance between each example and the comparative example.
[0090] Note: "—" indicates that no test data was obtained for Comparative Example 2 because the ionic conductivity was too low to charge and discharge normally at a rate of 0.2C.
[0091] As can be seen from Table 1, compared with Comparative Examples 1-2, Examples 1-2 simultaneously exhibit higher ionic conductivity, higher initial coulombic efficiency, excellent cycling performance, and lower interface impedance growth rate, indicating that this application significantly improves the interface stability and cycling performance of solid-state batteries.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0093] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, in the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
Claims
1. A composite solid electrolyte, characterized in that, include: Framework materials, deep eutectic electrolyte, polymers, and interface additives; The backbone material includes fast ion conductors and ceramic fillers, and the materials forming the polymer include curable monomers and initiators; The composite solid electrolyte includes a first surface and a second surface arranged opposite to each other, the first surface facing the negative electrode and the second surface facing the positive electrode; the pore size of the first surface is smaller than the pore size of the second surface.
2. The composite solid electrolyte according to claim 1, characterized in that, The fast ion conductor includes at least one of LLZO, LATP, and LAGP; And / or, the ceramic filler includes at least one of AlF3, BN, MgO, and TiO2; And / or, the mass ratio of the fast ion conductor to the ceramic filler is (5-9):(1-5); And / or, the mass of the fast ion conductor and ceramic filler accounts for 30% to 60% of the total mass of the fast ion conductor and ceramic filler, deep eutectic electrolyte, curable monomer, and initiator.
3. The composite solid electrolyte according to claim 1, characterized in that, The deep eutectic electrolyte includes a lithium salt, a hydrogen bond donor, and a hydrogen bond acceptor; And / or, the lithium salt includes at least one of LiTFSI, LiFSI, LiPF6, and LiClO4; And / or, the hydrogen bond donor includes at least one of urea, acetamide, glycerol, and ethylene glycol; And / or, the hydrogen bond acceptor includes at least one of succinic anionylene, choline chloride, choline bromide, and tetrabutylammonium chloride; And / or, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor and the lithium salt is 1:(1.5-3):(0.1-0.6).
4. The composite solid electrolyte according to claim 1, characterized in that, The curable monomer includes at least one of acrylate monomers, epoxy monomers, and olefin monomers; And / or, the mass of the curable monomer accounts for 1% to 5% of the total mass of the deep eutectic electrolyte and the curable monomer; And / or, the initiator accounts for 0.1% to 1% of the total mass of the deep eutectic electrolyte, the curable monomer, and the initiator.
5. The composite solid electrolyte according to any one of claims 1-4, characterized in that, The interface additive includes at least one of tin halide, bismuth halide, and zinc halide; And / or, the mass of the interface additive accounts for 0.1% to 5% of the total mass of the raw materials forming the composite solid electrolyte; And / or, the thickness of the composite solid electrolyte is 50 μm to 300 μm.
6. A method for preparing a composite solid electrolyte as described in any one of claims 1-5, characterized in that, include: Lithium salt, hydrogen bond donor and hydrogen bond acceptor are mixed and heated and stirred until a clear, transparent and homogeneous liquid is obtained, which is a deep eutectic electrolyte; The deep eutectic electrolyte, curable monomer, initiator, interfacial additive, fast ion conductor and ceramic filler are mixed to obtain a slurry; The slurry is injected into a mold, and the slurry is frozen and solidified under a unidirectional temperature gradient to obtain a frozen preform; The frozen preform is freeze-dried to obtain a porous intermediate. The porous intermediate is solidified to obtain a composite solid electrolyte.
7. The method for preparing the composite solid electrolyte according to claim 6, characterized in that, When preparing the deep eutectic electrolyte, the heating temperature is 40℃~90℃; And / or, the temperature difference of the unidirectional temperature gradient is 20℃~70℃; And / or, the preparation of a frozen preform includes: injecting the slurry into a mold, placing the bottom of the mold on a cold source at -40°C to -10°C, exposing the upper part of the mold to a preset temperature environment, wherein the preset temperature is higher than the temperature of the cold source, forming a unidirectional temperature gradient, and allowing it to stand for 2 to 8 hours to obtain a frozen preform.
8. The method for preparing the composite solid electrolyte according to claim 6 or 7, characterized in that, The freeze-drying process is carried out at a temperature of -60℃ to -40℃, under a vacuum of 5Pa to 20Pa, and for a duration of 24 to 72 hours. And / or, the solidification treatment of the porous intermediate includes: irradiating the porous intermediate with ultraviolet light to solidify the porous intermediate and obtain a composite solid electrolyte, wherein the wavelength of the ultraviolet light is 200-400 nm and the irradiation time of the ultraviolet light is 10-60 minutes.
9. A solid-state battery, characterized in that, The solid-state battery includes a positive electrode, a negative electrode, and a composite solid-state electrolyte disposed between the positive electrode and the negative electrode. The composite solid-state electrolyte is the composite solid-state electrolyte according to any one of claims 1-5 or a composite solid-state electrolyte prepared by the preparation method according to any one of claims 6-8.
10. An electrical appliance, characterized in that, The electrical device includes the solid-state battery as described in claim 9.